Defense Philosophy Perspectives on the Action of the Indonesian Defense Forces Army (PETA) in Blitar in Indonesian History Education Curriculum - Mochammad Ferdion Firdaus; Agus Sudarya; George Royke Deksino (The Republic of Indonesia Defense University, 2023)
The action of the PETA Army in Blitar in the curriculum of history education in Indonesia is classified as a series of rebellion events. The usage of the phrase rebellion equates the PETA Army Action in Blitar with post-independence rebellion operations. Conceptually, this narrative raises the dilemmatic question of whether heroic actions can be considered acts of rebellion at the same time. From a defense science perspective, the discourse on acts of rebellion is classified as acts of insurgency. An act of rebellion is a criminal act that cannot be allowed. As a result, people are trapped in terms that have negative connotations in describing PETA's heroic struggle in Blitar. Therefore, this paper seeks to straighten out this perspective so that =narratives of history education can be in accordance with defense science. The method used in writing this research uses a descriptive qualitative research method with a literature study approach with a variety of literature on the philosophy of defense, philosophy of conflict, and philosophy of peace. The results show that rebellion against legitimate authorities can be categorized as a criminal act or social pathology and must be combated. Meanwhile, rebellion in the sense of revolution to achieve independence in the view of defense philosophy is an effort to achieve peace in the life and security of a nation. This kind of action is in accordance with defense objectives. Based on this, the actions taken by the PETA Army in Blitar were an independence movement to resist colonialism. This research encourages the adjustment of terms in the narrative of historical learning related to the actions of PETA soldiers in Blitar to be clearer, fairer, and more responsible